Koranexegese als »Mix and Match«: Zur Diversität aktueller Diskurse in der tafsir-Wissenschaft - Poya, Abbas (transcript, 2017)
Studying the Koran is not only a central interest of Muslim erudition but also important in order to understand the intellectual-religious backgrounds of the various – fundamentalist, liberal, traditional and modern positions – within the Islam. This book discusses the textual hermeneutic approaches in different regions of the Islam – from Turkey, Egypt, Syria and Iran to India. The contributions outline the Koran exegesis as mix-and-match hermeneutics various players with different interests, methodical approaches and life experiences participate in. This way the plurality in Islamic thinking and acting is taken for granted, one of its reasons being the different approaches to the Koran.